A review on sugar and organic profiles on the postharvest quality of fruits / Nur Hidayatul Fatihah Johari ... [et al.] - Johari, Nur Hidayatul Fatihah; Dolhaji, Noer Hartini; Shamsuri, Shampazuraini; Abdol Latif, Phatimah (Faculty of Applied Sciences, 2023)
Sugar and organic acids are abundant constituents of ripe fruits. They are responsible for the sweetness and sourness of fruit; hence they contribute towards the postharvest quality, especially the physical characteristics and flavors. Sugars play a key role in fruit quality, as they directly influence taste and determine consumer acceptance. The most abundant sugars in many fruits are sucrose, glucose, and fructose, while organic acids are malic and citric acids. This review aims to provide information about sugar metabolism after postharvest. Metabolic changes in mature or senescent fruits during postharvest storage cause a general degradation in qualitative characteristics, including diminishing flavors and forming off- aroma compounds. Sucrose is created and transported from photosynthetically active leaves (sources) to non-photosynthetic tissues (sinks), such as developing seeds, fruits, and tubers. Secondly, to analyze the relationship between organic acid content and sugar content that affect the postharvest quality of fruits. The metabolic mechanisms employed in fruit synthesis, sugar metabolism, and malic and citric acid dissimilation are discussed. The activities of malic and citric acids in fruit flesh are also deliberated. In this review, citric acid was found to be predominated in acidic fruits, while malic acid surpassed it in acidic ones. Fructose substituted citric acid in acidless fruit and could be produced directly from citric acid or indirectly from glucose.